LNMAT1 Promotes Invasion-Metastasis Cascade in Malignant Melanoma by Epigenetically Suppressing CADM1 Expression - Mou, Kuanhou; Zhang, Xiang; Mu, Xin; Ge, Rui; Han, Dan; Zhou, Yan; Wang, Lijuan (Frontiers in Oncology, 2019)
Invasion-metastasis cascade is one of the most important factors relating to poor survival and prognosis of malignant melanoma (MM) patient. Long non-coding RNA lymph node metastasis associated transcript 1 (LNMAT1) is a key regulator in lymph node metastasis of multiple types of cancers, but the roles and underlying mechanisms of LNMAT1 in invasion-metastasis cascade of MM remain unclear. In the present study, we were interested to investigate the expression and function of LNMAT1 in MM. Here, we found LNMAT1 was upregulated in tissues and cells of MM, and its expressions were further enhanced in MM patients with lymph node metastasis and metastatic MM cells. Using loss-of function assays, we identified LNMAT1 promoted cell migration and invasion and lung metastasis in MM in vitro and in vivo. Moreover, we found cell adhesion molecule 1 (CADM1), the established tumor suppressor in MM, was the downstream targets of LNMAT1. Mechanistically, LNMAT1 epigenetically suppressed CADM1 expression by recruiting EZH2, the key regulator of trimethylation of histone H3 at lysine 27 (H3K27me3), to CADM1 promotor, which resulted in transcriptional inhibition of CADM1. In the last, rescue assays demonstrated that LNMAT1 promoted cell migration and invasion of MM via suppressing CADM1 expression. Our findings elucidate a new mechanism for LNMAT1-mediated invasion-metastasis cascade in MM, and suggested LNMAT1 may be a new therapeutic target and prognostic predictor for MM.